Uterine microbial communities and their potential role in the regulation of epithelium cell cycle and apoptosis in aged hens - Dai, Dong; Wang, Jing; Zhang, Haijun; Wu, Shugeng; Qi, Guanghai (Microbiome, 2023)
BackgroundAlterations of the uterine microbiome are closely associated with various intrauterine diseases and physiological conditions, which are well-established in mammals. However, as representative oviparous animals, the research on the uterine microbial ecosystem and its functions with physiological homeostasis is limited in chickens. Additionally, continuous egg-laying disrupts the oviducal immune defenses of aged hens, susceptible to pathogen invasion, causing poor egg quality and food-borne infections in humans. Here, we investigated aging-related changes in the oviduct microbial colonization and transmission from the gut to eggs and their roles in a hen model.ResultsThe results of 16S rDNA sequencing showed significant differences in the oviduct microbial composition between young (38 weeks) and aged (77 weeks) laying hens. SourceTracker analysis further revealed differences in the effects of microbial transmission on the oviducal microbiota between young and aged hens. Enhanced barrier defense with cell apoptosis suppression and cell cycle arrest of the uterus were observed in aged hens reducing microbial transmission from the lower to upper reproductive tract. In addition, a total of 361 significantly differential metabolites were identified using metabolomics in the aged uterine microbiota, especially in products of amino acid metabolism and biosynthesis of various secondary metabolites, which might have essential effects on cell apoptosis by regulating immune responses and cell cycle. Notably, antibiotics disrupted uterine microbiota by dietary intervention and direct perfusion did not retard aging-related physiological changes but further aggravated aging processes by disrupting the cell cycle and apoptosis.ConclusionsThe microbiota continuum along the reproductive tract in aged birds differs from that in young birds, especially with a significant shift in the uterus. The aged uterine microbiota probably contributes to the regulation of cell cycle and apoptosis by microbial metabolites primarily involved in amino acid metabolism and biosynthesis of various secondary metabolites. These findings provide new insights into the roles of the reproductive tract microbiota in regulating the cell programming of the aged host, contributing to the exploration of the microbiome as a target for diagnosing aging health status and therapy for gynecological diseases in women.Video Abstract